SELF DIRECTED LEARNING BERBASIS LITERASI DIGITAL PADA MASA PANDEMI COVID-19 DI MADRASAH IBTIDAIYAH - Elya Umi Hanik (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2020)
Abstract: The Implementation of Educational Policy in the Corona Virus Disease Emergency Period, requires educators to make a learning innovation, namely learning self directed learning based on digital literacy. This study aims to discuss 1) the concept of self directed learning, 2) the concept of digital literacy, 3) analysis of self directed learning based on digital literacy based on the co-19 pandemic at Madarasah Ibtidaiyah. This type of research used in this study is a qualitative study of literature approach with technical content analysis, the results of this study are 1) Self directed learning learning is independent learning to increase the responsibilities of students in the learning process. 2) Digital literacy is the knowledge and skills to use digital media, communication tools, or networks in finding, evaluating, using, making information, and using it in a healthy, wise, intelligent, accurate, precise, and law-abiding manner in order to foster communication and interactions in everyday life. 3) implement the implementation of digital literacy-based self direct learning during the Covid-19 pandemic, as follows; Provision of Educative Sites as School Community Learning Resources, Use of Educational Applications as School Community Learning Resources and online learning by making learning programs from home that are broadcast through the National TV channel of the Republic of Indonesia by the Ministry of Education and Culture       Abstrak: Pelaksanaan Kebijakan Pendidikan dalam Masa Darurat Corona Virus Disease, menuntut pendidik untuk melakukan sebuah inovasi pembelajaran, yaitu pembelejaran self directed learning berbasis literasi digital. Penelitian ini bertujuan untuk membahas 1) konsep pembelajaran self directed learning, 2) konsep literasi digital, 3) analisis self directed learning berbasisi literasi digital pada masa pandemi covid-19 di Madarasah Ibtidaiyah. Jenis penelitian yang digunakan dalam penelitian ini adalah studi kepustakaan pendekatan kualitatif dengan teknis analisis isi, hasil penelitian ini adalah 1)Pembelajaran self directed learning adalah  belajar mandiri untuk meningkatkan tanggung jawab peserta didik dalam proses pembelajaran. 2)Literasi digital adalah  pengetahuan dan kecakapan untuk menggunakan media digital, alat-alat komunikasi, atau jaringan dalam menemukan, mengevaluasi, menggunakan, membuat informasi, dan memanfaatkannya secara sehat, bijak, cerdas, cermat, tepat, dan patuh hukum dalam rangka membina komunikasi dan interaksi dalam kehidupan sehari-hari. 3)mplementasikan pelaksanaan pembelajaran self direct learning berbasis litersi digital pada masa pandemi Covid-19, sebagai berikut; Penyediaan Situs-Situs Edukatif sebagai Sumber Belajar Warga Sekolah, Penggunaan Aplikasi-Aplikasi Edukatif sebagai Sumber Belajar Warga Sekolah dan pembelajaran daring dengan membuat progam belajar dari rumah yang ditayangkan melalui saluran TV Nasional Republik Indonesia oleh Mendikbud